Opening and initial activity of faculty clinicsof the Siberian State Medical University - F. F. Tetenev; A. I. Karzilov (Бюллетень сибирской медицины)
Detailed data concerning opening and initial activity of faculty clinics of the Siberian State Medical University, data on the Siberian school of therapists are presented in the article.